(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
The power system transient stability studies depend on the state of sudden disturbance to which the system is subjected, such as the fault state on the system. The increasing size of modern power systems requires fast and more efficient methods of solutions. Therefore the classical approach of repeated integrations will be length and time consuming. Investigations to overcome this difficulty led to the use of direct methods. These methods use the energy balance in the system. This review paper presents the comparative study between the various energy function methods: Extended Equal Area Criterion (EEAC) method, Potential Energy Boundary Surface (PEBS), Relative Unstable Equilibrium Point RUEP, method with the Indirect Integration method of transient stability analysis .the methods was tested on test system 4-machine-six node and seven lines. For transient energy function transient energy and critical energy of the system are calculated in order to judge the stability of the system . In this study it was concluded that the Energy function methods not only avoid the time consuming solutions required in the conventional method, but also provide a quantitative measure of the degree of system stability and the PEBS method is suggested, It achieves more accurate values than other two methods (EEAC, RUEP)and confirms the traditional method